PENERAPAN KONSEP PLAYFUL DALAM PERANCANGAN RUMAH TUMBUH KEMBANG ANAK DI KAWASAN CASA JARDIN, JAKARTA BARAT - Hanny, Marcella; Suteja, Mekar Sari (Jurusan Arsitektur dan Perencanaan, 2024)
Early childhood, often referred to as the golden age, represents a critical period in a child's development that spans from birth to eight years old. During this time, children undergo rapid growth and development, shaping moral, religious, physical, social, emotional, linguistic, artistic values, and acquiring knowledge and skills appropriate to their developmental stages. In relation to this crucial phase, known as the